Lumpy skin disease virus 001/156 protein is a virulence factor that suppresses interferon production through impairing IRF3 dimerization. - Minmin Zhang; Yujie Shi; Xinyin Lu; Qiwei Zhang; Yubo Zhao; Shaohan Li; Zhiyuan Wen; Jinying Ge; Xijun Wang; Jie Li; Zhigao Bu; Xin Yin (PLoS Pathogens, 2025)
Lumpy skin disease virus (LSDV), a member of the genus Capripoxvirus within the family Poxviridae, causes significant disease in cattle and is classified as a notifiable disease by the World Organization for Animal Health (WOAH). The virus contains a double-stranded linear DNA genome of approximately 151 kbp, encoding 156 predicted open reading frames (ORFs) for various proteins. However, only a limited number of these proteins have been characterized, with the functions of many-particularly those encoded within the inverted terminal repeat (ITR) regions-remaining largely unknown. In this study, we utilized homologous recombination to generate LSDV mutants with deletions of the LSDV 001/156 gene to investigate its role. LSDV 001/156, an uncharacterized protein located within the ITR region, was identified as a late-expressed gene product incorporated into virions and involved in viral replication. Further analysis revealed that LSDV 001/156 acts as a negative regulator of the interferon (IFN) signaling pathway. It interacts with interferon regulatory factor 3 (IRF3), disrupting its dimerization and nuclear translocation, thereby attenuating IFN production. Functional studies demonstrated that the LSDV mutant lacking the 001/156 gene exhibited reduced replication and virulence in cattle compared to the wild-type virus, likely due to enhanced IFN responses in the absence of this immune-evasive protein. In summary, our findings uncover a novel role of the LSDV 001/156 gene in modulating the host intrinsic antiviral response, shedding light on the mechanisms underlying LSDV pathogenesis. This study highlights the importance of ITR-encoded genes in immune evasion and virulence, providing new insights into LSDV biology and its interactions with the host immune system.